Proteomic methods for separation and identification of milk proteins - O. V. Lepilkina; A. I. Grigorieva (Пищевые системы, 2025)
The review presents the most common proteomics methods based on separation and identification of proteins, with examples of their use for studying the protein system of milk and dairy products. The essence of electrophoretic and chromatographic methods for separating proteins and peptides and their identification using Western blotting and mass spectrometry is described. The main types of electrophoresis methods (native, two-dimensional, in polyacrylamide gel with urea, immunoelectrophoresis, capillary) and chromatography methods (gas, liquid, ion exchange, gel filtration, affinity) are given. It is noted that the main direction of research using these methods, which has both scientific and applied significance, is the detection of falsifications in the composition of milk and dairy products. Such falsifications are associated with the deliberate addition of dry milk and cheese whey, as well as with the replacement of raw milk by milk from other animals, which is unacceptable in the production of cheeses with a protected designation of origin (PDO) or a protected geographical indication (PGI). Another area is research into the proteolytic processes that occur during the maturation of cheeses, on the basis of which their degree of maturity and species can be determined depending on the manufacturing technology. Given the wide range of cheeses from different countries, such research is clearly insufficient.